(untitled) (TẠP CHÍ KHOA HỌC TRƯỜNG ĐẠI HỌC TRÀ VINH, 2023)
The rearing experiment of tire track eel (Mastacembelus favus) in the recirculating aquaculture system was conducted at the Freshwater Experimental Research Station, Tra Vinh University from April to June 2022. The experiment concluded four treatments: two experimental treatments in a recirculation aquaculture system with the rearing density of 1,500 individuals/m3 for the first experiment and 2,000 individuals/m3 for the second experiment, two control treatments in a free water system with 1,500 individuals/m3 for the first control and 2,000 individuals/m3 for the second control, and each treatment was designed with triplicates. The fry with an average initial weight of 0.016 g/fish and an average length of 1,033 cm/fish were reared in the 500-L composite tank. Fish were fed with Moina, worms and pellets (40% protein) and the feed was adjusted to the needs of fish in each treatment. After 60 days of rearing, the highest growth rate was at the first experiment (0.019 g/day and 7.08%/day) and was significantly higher than the two control treatments (p > 0.05). The second control treatment had the lowest growth rate (0.010 g/day and 6.11%/day). The first experiment had the highest survival rate (50.6%), which was significantly different (p < 0.05) from the second experiment (38.9%) and the second control treatment (33%). Thus, rearing fry of tire track eel in the recirculating aquaculture system with a stocking density of 1,500 individuals/m3 achieved the best results.